CLEAN PRODUCTION OF COMMERCIAL FREEZE–DRIED MANGOSTEEN POWDER FOR MEDICINAL HERB AND NUTRITIONAL HEALTH BENEFITS - Chaisawadi, S; Methawiriyasilp, W. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Mangosteen (Garcinia mangostana) is one of the important medicinal plants in Thailand, which all parts provide a whole range of medicinal properties and high nutritional value. Xanthones, a potent antioxidant in mangosteen have been shown to have extensive biological and pharmacological activities, make it a potential candidate for commercial production. The clean production of freeze-dried mangosteen powder has been designed by using clean technology to serve the need of zero discharge during the process. The wastes from freeze drying process, which are the xanthone-packed pericarp have been considered to utilize as a medicinal herb and nutritional health products. The designed processing in this study consists of freeze drying process and waste utilization process. The freeze-drying process has been done on mangosteen flesh and seed by blending and freeze drying to powder. The waste utilizing process has been divided into two processes, the inner pericarp processing and outer pericarp processing. The inner pericarp processing has been done by scalping the inner pericarp and blending, followed by freeze drying to get the inner pericarp powder and use for nutritional health products. The outer pericarp processing has been done for xanthone extraction by cutting into small pieces, tray drying, grinding into powder and ethanol extraction for medicinal and cosmetic used. The residue of the outer part pericarp and other wastes can be used as biopesticide or fertilizers. The clean production on mangosteen powder processing has been implemented by Fruit Processing Pilot Plant, Industrial Park, KMUTT. The pilot results showed all parts of mangosteen have commercial used and nothing goes to waste. The pilot data showed high productivity along with low environmental impact. The preliminary study on financial analysis showed high feasible for commercial production. Acknowledgements: Thanks to Thai Government Budget Fund 2007 for Financial Supports